2003
DOI: 10.1007/s00464-002-9173-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of benign gastrointestinal anastomotic strictures using argon plasma coagulation in combination with diathermy

Abstract: Endoscopic argon plasma coagulation in combination with diathermy is a safe and effective technique for the treatment of short postsurgical gastrointestinal anastomotic strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…This method is a form of non-contact electrocoagulation, and one of the advantages of APC is the outstanding long-term efficacy [24,25]. In our study, the efficiency of the APC group was clearly better than that of the SB group after one month (ER: 80 vs. 20%) and three months (ER: 20 vs. 3.3%).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…This method is a form of non-contact electrocoagulation, and one of the advantages of APC is the outstanding long-term efficacy [24,25]. In our study, the efficiency of the APC group was clearly better than that of the SB group after one month (ER: 80 vs. 20%) and three months (ER: 20 vs. 3.3%).…”
Section: Discussionmentioning
confidence: 48%
“…In our study, the efficiency of the APC group was clearly better than that of the SB group after one month (ER: 80 vs. 20%) and three months (ER: 20 vs. 3.3%). In addition, another attractive characteristic of APC is easy to practice for endoscopists and the process of APC performed is only 10-15 min [24,25], which is considerably more rapid than laser therapy and microwave tissue coagulation [20,28]. APC is clearly more ideal as it shortens the operating time for endoscopists and also reduces patient discomfort in the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schubert et al used argon plasma coagulation combined with diathermy to treat 49 patients with anastomotic strictures. 52 They used electroincision to create flaps and then argon plasma coagulation to reduce the size of the flaps, which resulted in dilatation of the gastrointestinal lumen at the location of the stricture. Although this was not specifically preformed for anastomotic strictures following RYGB, they reported that 92% of patients required only one treatment session to gain long-term recanalization.…”
Section: The Role Of Endoscopy Postoperative To Detect and Treat Anasmentioning
confidence: 99%